2014
DOI: 10.1016/j.jval.2014.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Role of Corticosteroids Use in Ards: Comparison of Systematic Review and Meta-Analysis

Abstract: Objectives: Anti-cancer chemotherapeutic pharmaceutical agents have some toxic effects to normal cells. Therefore, the main factors to increase therapeutic effects are to destroy cancer cells specifically and appropriate dosage of anticancerous agents. Cancer cells are have being studied in many ways by using cell culture technologies in developed countries. We aimed to determine the chemosensitivity of colorectal cancer cases. MethOds: From February 2013 through February 2014, Histoculture drug response assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Multiple meta-analyses in patients with ARDS observed that steroids reduce mortality, reduce ventilation duration, and increase ventilator-free days [86][87][88]. A Cochrane meta-analysis observed benefits of 90-day mortality reduction and improved ventilator-free days with steroids compared to placebo [89].…”
Section: Steroidsmentioning
confidence: 99%
“…Multiple meta-analyses in patients with ARDS observed that steroids reduce mortality, reduce ventilation duration, and increase ventilator-free days [86][87][88]. A Cochrane meta-analysis observed benefits of 90-day mortality reduction and improved ventilator-free days with steroids compared to placebo [89].…”
Section: Steroidsmentioning
confidence: 99%